(untitled) (Journal of Governance and Development (JGD), 2015)
One of the efforts developed by the government in optimizing and developing the potential of the region by creating, driving, and encourage the presence of Small and Medium Enterprises (SMEs). In connection with these efforts, the Indonesian government through the provision of capital assistance to facilitate SMEs by creating a revolving fund program. The fund of this program allocated by the Ministry/Agency/Unit General Services Agency for the strengthening of venture capital for cooperatives, micro, small, medium, and other efforts under the guidance of State Ministries/Institutions (Ministry Decree No. 218/PMK.5/2009). By the help of a revolving fund is expected to be able to help strengthen the working capital needed to empower SMEs, increase economic activity, increase the business volume of SMEs, and improve employment and increase the spirit of entrepreneurship among the community. Considering SMEs has a crucial role in growing the economy of society, so that facilities revolving fund for SMEs will be a stimulus for economic dynamics in economic growth and the expected future output of SME products can contribute to economic growth and national income, creating a climate that strengthens the potential owned by the community with the provision of a wide range of access to wider opportunities and to prevent competition by creating expectations of future partnerships and the other expected future is SME products are competitive in the international market.